Roles for IBA-derived auxin in plant development - Frick, Elizabeth M (Journal of experimental botany, 2018)
© The Author(s) 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.